If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -22 = 62 + 2x Reorder the terms: -22 + 4x = 62 + 2x Solving -22 + 4x = 62 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -22 + 4x + -2x = 62 + 2x + -2x Combine like terms: 4x + -2x = 2x -22 + 2x = 62 + 2x + -2x Combine like terms: 2x + -2x = 0 -22 + 2x = 62 + 0 -22 + 2x = 62 Add '22' to each side of the equation. -22 + 22 + 2x = 62 + 22 Combine like terms: -22 + 22 = 0 0 + 2x = 62 + 22 2x = 62 + 22 Combine like terms: 62 + 22 = 84 2x = 84 Divide each side by '2'. x = 42 Simplifying x = 42
| -z+1=2-3y-x | | 3(x-2)-4(x+4)=-2(x-6) | | -14+3(x+10)=7(2x+5)-4 | | -7(6-7b)+6=-134 | | Z-2-3y=2x | | 6x-18=5x+15 | | h-49=13.8 | | 3x-1=7-3y+2 | | 16+144t+324t^2=0 | | 3(x-20)-4(x+4)=-2(x-6) | | 4c(a-6)+7(a-6)= | | X+2x=1050 | | -6(-1)-2y=12 | | 8c-7c=16 | | 2x+6(1+5x)=230 | | (2x-7/4)=0 | | 25=k/5;k=5 | | x-3+2x=33 | | 8-5x=42 | | -2(3-5k)=-76 | | -5p-3(-p)-p=4 | | -7(x-7)=-84 | | .13x+14.95=.39x-15.00 | | Lg(3x-5)=-3 | | -5(3-7x)=-85 | | 4(-3m+2)=32 | | 40=32t | | 2n+8n-13=17 | | 1=w/6 | | (2v*3*4v)^4/2v^4 | | .39x-15.00=50 | | 5x-45=90 |